The Determination of Unemployment Benefits - Di Tella, Rafael; MacCulloch, Robert J. (Journal of Labor Economics, 2002)
While much empirical research exists on labor market consequences of unemployment benefits, there is remarkably little evidence on the forces determining benefits. We present a simple model where workers desire insurance against unemployment risk and benefits increase the unemployment rate. We then conduct one of the first empirical analyses of the determinants of the parameters of the benefit system. Using data for developed countries for 1971–89, controlling for year and country fixed effects and the government's political color, we find evidence that the level of benefits falls when the unemployment rate is high. This is consistent with Wright's tax effect.